Social Identity and Group Dynamics in Physical Development: Selection and Application of General Physical Exercises for Second-Year Students at Hanoi Capital University - Nhu Quynh , Luu Thi (Environment and Social Psychology, 2025)
This study investigates the influence of social identity theory and group dynamics on exercise adherence and motivation among second-year Physical Education majors. Findings indicate that training activities enhancing positive group identification substantially boost collective efficacy and peer-driven motivation. Students engaged in socially cohesive exercise programs achieved 25-30% greater physical improvement than those following individually oriented protocols. The analysis further shows that social-psychological variables account for roughly 40% of the variance in performance gains. These results highlight the essential function of group belonging and shared identity in shaping sustainable training engagement. Overall, the study affirms that social context is not merely supportive but a core determinant of physical development outcomes in higher-education settings.